Phase detection method embedded devices in telephone line - Хома, Володимир Васильович; Іванюк, Віталій Миколайович (Ukrainian Information Security Research Journal, 2015)
Interception of telephone communications and listening rooms equipped with telephones is the most likely threats to information security telecommunication subscribers. Although developed many methods and identify telephonebugs, but given the development of information technology, the search for new methods of detecting unauthorized connections to ATL. Design and investigate of linear bridge adapter for detecting unauthorized connectionsto telephone lines is described in this article. Ablock diagram of device for implementing the phase detection method of telephone bags is shown. A mathematical model of the linear adapter is developed and an efficiencyof its operations is analyzed. The synchronousdetection using for increasing of the device noise immunityis augmented.